How do early traumatic experiences/emotional pain inform Counsellors career choice? - Panagiotopoulou, Anthi (2014)
Abstract This study examined how early traumatic or difficult life experiences impact on counsellor’s choice of career and how they influence the therapeutic work with clients. Semi-structured interviews were conducted on a voluntary basis with three fellow MA counselling students who had already commenced working with clients. The interviews were transcribed and analysed qualitatively. Participants referred to their early traumatic experiences as their main motivation to enter the counselling profession. Traumatic experiences were defined as: physical and emotional child abuse, witnessing parental conflicts, early loss and deprivation. The impact of trauma on both childhood and adult life was explored. Participants underscored the importance of their personal growth following adversity and the positive impact of their life experiences on their professional practice. The development of empathy, compassion and resilience were particularly emphasized. Finally, implications for practice as well as some recommendations for future research are discussed.